Mapping Movie Magazines
XXIX, 324 p.
Keywords: “Mapping Movie Magazines is an exciting and timely collection on uncharted regions and approaches, richly demonstrating that movie magazines are emphatically not a secondary or peripheral part of cinema history but are woven into its very fabric.” - Michael Williams, Professor in Film Studies, University of Southampton “This reader brings what was once regarded as a peripheral aspect of cinema culture and scholarship back to the center of analysis through an international collection of engaging and revealing essays. This volume will be a model for further research, as the digitization of these fascinating materials proceeds apace.” - - Robert C. Allen, Professor in American Studies, University of North Carolina at Chapel Hill “Mapping Movie Magazines reveals how the increased accessibility through digitization of fan magazines and film trade papers presents exciting new opportunities for research.” - - Annette Kuhn, Emeritus Professor in Film Studies, Queen Mary University of London Movie magazines are crucial but widely underused sources for writing the history of films and cinema. This volume brings together for the first time a wide variety of historic research of movie magazines and film trade journals, reflecting on the issue of using these sources for film/cinema historiography and on the impact of digitization processes. Mapping Movie Magazines explores this debate from different disciplinary perspectives, enlightened by case studies from the use of early film trade press to pedagogical uses of digitized periodicals. The volume explores Hollywood’s grip on movie magazines, gender in film journalism, typologies of unknown trade press and movie magazine markets, and subversive Tijuana bibles.